2017
DOI: 10.11648/j.ijsts.20170504.22
|View full text |Cite
|
Sign up to set email alerts
|

A New Procedure for Porous Material Characterization

Abstract: Abstract:A new procedure for quantitative characterization of different types of solid materials is proposed. The technique is based on the Scanning Electron Microscopy (SEM) analysis results of porous materials and their processing by the software ImageJ. Several types of porous adsorbents AX21, AC35, GAC250, ACENO and IRH3 activated carbons were investigated. Based on SEM analysis, different characteristics of the samples such as porosity, pore size distribution, bed particles porosity can be obtained. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The presence of typical patterns of ZnCl2 and HNO3 suggested that the washing process should be improved. The SEM images in Figure 3 provide surface morphology and pore size of the samples [21]. It can be seen that the activated carbon (CEA) sample formed few microporous.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of typical patterns of ZnCl2 and HNO3 suggested that the washing process should be improved. The SEM images in Figure 3 provide surface morphology and pore size of the samples [21]. It can be seen that the activated carbon (CEA) sample formed few microporous.…”
Section: Resultsmentioning
confidence: 99%
“…This geometry is expected for the TiO 2 particles Guo D et al, 2020;Pan K et al, 2011;Barbé CJ et al,1997;Ni M et al, 2006). To obtain the information about the average diameter and the porous distribution, the software ImageJ, broadly used in research, was applied (Figure 5a, b and c, Table 1) (Chilev C et al 2017).…”
Section: Sem (Scanning Electron Microscopy) and Eds (Energy Dispersiv...mentioning
confidence: 98%
“…In application of powder plasma coating, controlling the microstructural parameters of the coating, such as the desired structural-phase composition, the required porosity and morphology are of significance. In many cases, the study of the structure of coatings, for example, their * corresponding author; e-mail: dalontseva@mail.ru porosity is carried out using scanning microscopy [5,6]. One of the main methods of analysis of the structuralphase composition of coatings, is using the X-ray diffraction [7,8].…”
Section: Introductionmentioning
confidence: 99%